Addressing Supervisory Feedback: An Autoethnographic Account of a Doctoral Candidate in Nepal - Khati, Ashok Raj (Journal of Tikapur Multiple Campus, 2026)
Supervisory feedback serves as a central mechanism for academic growth guiding doctoral students towards producing a dissertation with scholarly standards. However, there is a little focus in Nepali higher education context on how doctoral candidates experience, interpret and transform by engaging with supervisory feedback. This study explores my lived experiences of addressing and engaging with supervisory feedback in the final year of my PhD. It further investigates how this engagement with feedback of supervisor broadened my understanding of the research process and transformed my scholarly identity as a doctoral researcher. The data sources for this autoethnographic study included supervisor's comments and feedback texts supplemented by my memory, and dissertation drafts and revisions. The analysis proceeded chronologically, chapter by chapter. It traced my major responses thematically, generating interpretive categories that illuminated my transformation and scholarly becoming. Through this journey of engaging with supervisory feedback—from restructuring the research problem to refining the findings—I experienced a persistent cycle of rereading, revisiting, reflecting, rewriting, and realizing. Each round of comments required me revise more precisely, think more deeply and write more responsibly. The feedback process itself became as Adams (2018) stated as 'a flowing conversation' through which doctoral identity is shaped. The process not only refined my dissertation but also transformed me into a more reflective scholar and emerging academic writer.